Effects of oxygen on post-surgical infections during an individualised perioperative open-lung ventilatory strategy: a randomised controlled trial. (January 2020) - ,; Acosta, Jesús; Alberola, María J.; Alcón, Amalia; Almajano, Rosa; Álvarez, Carlos; Anaya, Rafael; Aragón, Cristian; Argilaga, Marta; Arocas, Blanca; Ayas, Begoña; Balandrón, Victor; et al.
Abstract: Background: We aimed to examine whether using a high fraction of inspired oxygen ( F IO2 ) in the context of an individualised intra- and postoperative open-lung ventilation approach could decrease surgical site infection (SSI) in patients scheduled for abdominal surgery. Methods: We performed a multicentre, randomised controlled clinical trial in a network of 21 university hospitals from June 6, 2017 to July 19, 2018. Patients undergoing abdominal surgery were randomly assigned to receive a high (0.80) or conventional (0.3) F IO2 during the intraoperative period and during the first 3 postoperative hours. All patients were mechanically ventilated with an open-lung strategy, which included recruitment manoeuvres and individualised positive end-expiratory pressure for the best respiratory-system compliance, and individualised continuous postoperative airway pressure for adequate peripheral oxyhaemoglobin saturation. The primary outcome was the prevalence of SSI within the first 7 postoperative days. The secondary outcomes were composites of systemic complications, length of intensive care and hospital stay, and 6-month mortality. Results: We enrolled 740 subjects: 371 in the high F IO2 group and 369 in the low F IO2 group. Data from 717 subjects were available for final analysis. The rate of SSI during the first postoperative week did not differ between high (8.9%) and low (9.4%) F IO2 groups (relative risk [RR]: 0.94; 95% confidence interval [CI]: 0.59–1.50; P =0.90]). Secondary outcomes, such as atelectasis (7.7% vs 9.8%; RR: 0.77; 95% CI: 0.48–1.25; P =0.38) and myocardial ischaemia (0.6% [ n =2] vs 0% [ n =0]; P =0.47) did not differ between groups. Conclusions: An oxygenation strategy using high F IO2 compared with conventional F IO2 did not reduce postoperative SSIs in abdominal surgery. No differences in secondary outcomes or adverse events were found. Clinical trial registration: NCT02776046.